An assessment of scientific impact of Indian journals. Issue 1 (2nd January 2018) - Ahmad, Shakil; Waris, Abu; Abdel-Magid, Isam Mohammed; Aqil, Mohammad
Abstract : The main objective of this research work is to assess the impact and visibility of Indian journals, estimate presently published (2017) scientific journal quality mostly adopted bibliometric indicators: Journal Impact Factor (JIF), Eigenfactor Score (ES), SCImago Journal Rank indicator (SJR) and H5. Indian journals were picked from their class from Web of Science. JIFs and ESs are obtained from Journal Citation Report and the SJR from the SCImago Journal and country rank website. The 106 Indian journals taken, analyzed and documented with conjoined required data retrieved from primary and original sites in linking JIF, SJR, ES and H5 quality indexes for quality ranking. Correlations among indicators were described by means of Pearson's and Spearman's statistical correlations through use of SPSS software. All graphed journals are indexed in noticeable and respected databases of Web of Science (WoS) and Scopus. Bivariate correlation between the selected indicators (JIF, ES, SJR and H5) for ranking of the selected Indian journals revealed that there is a high Pearson's (r) statistical correlation between JIF and H5 indicators